Decoding Gen Z’s Green Purchases: The Role of Product Attributes and Environmental Awareness - Barkah Barkah; Puty Febriasari Prasetyo; Erna Listiana (Dinasti Publisher, 2025)
Although Indonesian Generation Z demonstrates strong commitment to climate change mitigation, their actual green behavior remains limited. This study examines the influence of product attributes on green purchasing behavior, with environmental awareness as a mediating variable. Data were collected from 113 respondents representing Generation Z in Indonesia and analyzed PLS-SEM using SmartPLS 4. Findings indicate that product attributes positively influence environmental awareness, but environmental awareness does not directly or indirectly affect green purchasing decisions. Factors such as green product characteristics, ecological sensitivity, and environmental concern were found to shape sustainable purchasing behaviors among Indonesian Gen Z. Theoretically, this research expands the understanding of green consumption patterns and clarifies the conceptual link between product attributes and environmental awareness in the Indonesian youth context. Practically, the study offers managerial insights and actionable recommendations to encourage green purchasing in this demographic.